Comparison of eugenol and dihydromyricetin loaded nanofibers by electro-blowing spinning for active packaging. (February 2023) - Liu, Songqi; Chen, Zaihan; Zhang, Huange; Li, Yuanli; Maierhaba, Taxipalati; An, Jianhui; Zhou, Zhi; Deng, Lingli
Abstract: To explore the dihydromyricetin or eugenol loaded nanofiber's potential as food active packaging, 0%, 0.1%, 0.5%, and 1.0% dihydromyricetin or eugenol loaded nanofibers were fabricated by electro-blowing spinning, which increased the yield of nanofibers by a factor of 10 times compared to that of traditional electrospinning. The morphology observation by scanning electron microscopy showed similar morphology and diameter distribution of the dihydromyricetin or eugenol nanofibers. Fourier transform infrared spectra analysis indicated that eugenol or dihydromyricetin interacted with proteins through hydrogen bonding. X-ray diffraction profiles of the nanofibers indicated that dihydromyricetin was uniformly distributed within the nanofibers. Nanofibers encapsulated with various concentrations of eugenol or dihydromyricetin showed better barrier properties against water vapors than the free nanofibers, which indicated that the hydrophobic eugenol and dihydromyricetin inhibited the permeation of water molecules through the nanofibers. Tensile tests showed that the nanofibers loaded with 0.5% eugenol or 1.0% dihydromyricetin exhibited relatively higher elastic moduli and lower elongation at break. The nanofibers loaded with dihydromyricetin showed comparable antioxidant activity to that with eugenol in the aspect of ferric and cupper reducing activity, while that with 0.1%–1.0% dihydromyricetin showed superior DPPH radical scavenging activity. Furthermore, both eugenol and dihydromyricetin loaded gelatin/zein nanofibers showed effective antimicrobial activities against Escherichia coli and Staphylococcus aureus . Overall, the dihydromyricetin loaded gelatin/zein nanofibers showed comparable physical and functional properties compared to eugenol, which suggests the application of dihydromyricetin nanofibrous films on food active packaging and the potential application of dihydromyricetin on functional food delivery systems. Graphical abstract: Image 1